Microelectromechanical systems - Versuh, Eve (NY Research Press, 2015)
This book is prepared by the specialists in the field of microelectromechanical systems (MEMS). It consists of two major sections dedicated to BioMEMS Devices, and MEMS characterization and micromachining. The developments of MEMS and devices have been influential in the demonstration of new devices and techniques, and even in the influx of new fields of research and development such as BioMEMS, actuators, microfluidic devices, RF and optical MEMS. The experience signifies a need for MEMS book encompassing these materials along with the most important process steps in bulk micro-machining and modeling. This book commences with the evolving field of bioMEMS, discussing MEMS coil for retinal prostheses, DNA extraction by micro/bio-fluidics devices and acoustic biosensors.